2014
DOI: 10.1111/ahe.12109
|View full text |Cite
|
Sign up to set email alerts
|

Absent Left Main Coronary Artery with Variation in the Origin of its Branches in a South African Population

Abstract: Coronary artery anomalies are traditionally classified into anomalies of origin, course and termination. One of the anomalies of origin is absence of the left main coronary artery (LMCA), where the left anterior descending (LAD), the circumflex (Cx) and the ramus medianus (RM) (when present) arteries originate directly from the left aortic sinus. The study aimed to document the prevalence of absent LMCA, discuss its possible embryogenesis and clinical relevance. A review of 407 coronary angiograms performed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
0
8
1
Order By: Relevance
“…In these cases, left dominance was observed in all hearts and this variation was observed in more females (83.3%) than males (16.6%). This was lower than Ajayi et al [1], who found 20.5% of hearts presenting a split RCA with and an absent LCA. This study found left dominance to be more prevalent in the presence of a double or split RCA (85.7%).…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…In these cases, left dominance was observed in all hearts and this variation was observed in more females (83.3%) than males (16.6%). This was lower than Ajayi et al [1], who found 20.5% of hearts presenting a split RCA with and an absent LCA. This study found left dominance to be more prevalent in the presence of a double or split RCA (85.7%).…”
Section: Discussioncontrasting
confidence: 62%
“…Bogers et al [8] showed that coronary vessels develop by ingrowth towards their orifices on the ascending aorta which differs from the previous assumption that coronary arteries are formed by outgrowths from the aorta and the systemic venous sinus, respectively. Ajayi et al [1] suggested that the high prevalence of split RCA in hearts with absent LCA may be due to the occurrence of the fast ingrowth of the primitive coronary vascular network in both the left and right coronary vascular tree. The branches of the RCA may have joined to form a single trunk while approaching the right coronary ostium due to fast ingrowth in such hearts.…”
Section: Discussionmentioning
confidence: 99%
“…In 16.66% of the cases, this vessel did not present its origin from the aorta, but only its branches, a fact that has not been reported in literature. It was not observed absence of the left coronary artery, as reported in Syrian hamsters (Durán et al, 2006) and humans (Ajayi et al, 2015), or even the artery presenting itself duplicated (Kareem et al, 2014).…”
Section: Discussionmentioning
confidence: 46%
“…The right and left coronary arteries emerge from the aorta, each one presenting a single coronary ostium (Schummer et al, 1981;Ghoshal and Getty, 1986;Ghoshal, 1986, Valentina et al 2003and Oliveira et al, 2013. There are cases in calves and humans with only one coronary artery being responsible for the whole heart's irrigation, presenting only one ostium from the aorta (Cervený andKaman, 1963 andKoizumi et al, 2000) and in the Syrian Hamster and man, where the left coronary artery is absent, presenting only the branches originating from the aorta (Durán et al, 2006 andAjayi et al, 2015).…”
Section: Introduction mentioning
confidence: 99%
“…This may suggest that the LCA grows faster than the RCA during fetal development. Ajayi et al (2015), reported that 20.5 % of the patients with absent LCA had splitting of the RCA and suggested that in such patients during development of the coronary arteries there is fast ingrowth of the primitive coronary vascular network in both the left and right coronary vascular tree. Int.…”
Section: Discussionmentioning
confidence: 99%